Antimicrobial activity of eugenol against carbapenem-resistant Klebsiella pneumoniae and its effect on biofilms. (February 2020) - Qian, Weidong; Sun, Zhaohuan; Wang, Ting; Yang, Min; Liu, Miao; Zhang, Jianing; Li, Yongdong
Abstract: A preliminary study found that eugenol expressed an antibacterial activity against Klebsiella pneumoniae . However, the mechanism of action of eugenol against K. pneumoniae still remains unexplored. The aim of this study was to gain further insight into the antibacterial effect of eugenol against carbapenem-resistant Klebsiella pneumoniae (CRKP) and possible mode of action. Here, minimum inhibitory concentration (MIC) of eugenol against CRKP strains was determined using the agar dilution method. Moreover, variations in intracellular ATP concentration, intracellular pH (pHin ), membrane potential and membrane integrity were measured to evaluate the effect of eugenol on cell membrane. Besides, changes in cell structure and biofilm formation of CRKP as well as biofilm-associated cell damage were determined using field emission scanning electron microscope (FESEM), transmission electron microscope (TEM) and confocal laser scanning microscopy (CLSM). Finally, gene expression of biofilm-related biosynthesis was investigated. The results showed that MICs of eugenol against four tested CRKP were 0.2 mg/mL. Eugenol damaged the cell membrane of CRKP, as evidenced by decreased intracellular ATP concentration, reduced pHin and cell membrane hyperpolarization, coupled with enhanced membrane permeability. Furthermore, eugenol compromised cell structure and induced loss of intracellular components of CRKP. Additionally, eugenol inhibited biofilm formation and inactivated biofilm CRKP cells. Finally, eugenol presented strong inhibitory effects on biofilm formation and biofilm-associated gene expression, and inactivated CRKP cells growing in biofilms. These findings suggest that eugenol exhibits antimicrobial effect against CRKP strains and could be potentially used to control CRKP-related infections. Highlights: Eugenol presents inhibitory effect on biofilm formation of carbapenem-resistant K. pneumoniae . Eugenol down-regulates the relative expression of four biofilm-related genes of carbapenem-resistant K. pneumoniae . Eugenol demonstrates disruptive effect on carbapenem-resistant K. pneumoniae cell membrane. Eugenol kills carbapenem-resistant K. pneumoniae cells within biofilms.